Multiculturalism in Anita Nair’s Mistress - N.Tamilarasi; Andrew, Jasmine (International Journal of Psychosocial Rehabilitation, 2020)
Anita Nair is one of the prominent novelists in Indian English Literature. Her third novel is Mistress. Here Nair portrays about a woman character and her struggle in her life. Saadiya is one of the characters in the novel Mistress. She is a Muslim girl and she married a Hindu boy. The love affair of Sethu and Saadiya is depicted in the novel. The sufferings of Saadiya as a Muslim woman are also presented. Saadiya does not obey the words of her father and the other members of her family. Saadiya’s father advises her to marry a Muslim man. But Saadiya does not listen to her father’s advice. So he is worried about his daughter’s love affair with a Hindu boy. Saadiya turn a deaf ear to her family members’ advice, rules and regulations. The relationship between a man and woman is mentioned in Mistress. Saadiya suffers due to the difference of culture and religion. She leads an alienated life after marrying Sethu. She gives birth to a son named as Omar Masood. At last she commits suicide.